2020
DOI: 10.1088/1361-6579/abaa55
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electrical properties of ex vivo human hepatic tissue with metastatic colorectal cancer

Abstract: Objective: To probe the distribution of electrical properties in tumor-bearing human hepatic tissues with metastatic colorectal cancer. Approach: Electrochemical impedance spectroscopy (EIS) and a non-contact electromagnetic probe were used for distinguishing spatial heterogeneities in fresh, unfixed human hepatic tissues ex vivo from patients with metastatic colorectal cancer (CRC). Main results: Point-wise EIS measurements reported over a frequency range of 100 Hz–1 MHz showed that the interface tissue betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The heterogeneity observed in EV size distribution from the serum samples reflects the heterogeneity of this disease (Matthyssens et al., 2015). Tumor heterogeneity is also presented at the tissue level and has been reported for other types of cancer with 40% or higher variation in tumor properties reported between patients (Lochab et al., 2020; Prakash et al., 2015). In order to obtain insights to the heterogeneous size distributions a comparison of the difference between NTA of the same serum sample before and after the device rather than comparison of the sera samples across patients was reported in Figure 6.…”
Section: Discussionmentioning
confidence: 86%
“…The heterogeneity observed in EV size distribution from the serum samples reflects the heterogeneity of this disease (Matthyssens et al., 2015). Tumor heterogeneity is also presented at the tissue level and has been reported for other types of cancer with 40% or higher variation in tumor properties reported between patients (Lochab et al., 2020; Prakash et al., 2015). In order to obtain insights to the heterogeneous size distributions a comparison of the difference between NTA of the same serum sample before and after the device rather than comparison of the sera samples across patients was reported in Figure 6.…”
Section: Discussionmentioning
confidence: 86%
“…Currently, IRE is performed mostly for solid tumors such as liver cancer (12), pancreatic cancer (13), and prostate cancer (8) and provides an advantageous palliative treatment for advanced tumors in the vicinity of important ductal structures, such as large blood vessels, the intestines, bile ducts, or the urinary tract. However, the uneven distribution of the PEF, resulting from the heterogeneous electrical properties of tumor tissue (14,15), leads to incomplete ablation and increases the risk of tumor recurrence, which limits the popularity of IRE in clinical practice. Notably, the membrane perforation resulting from IRE can promote the massive release of intracellular concealed tumor antigens, inducing a potential antitumor immune response to kill residual tumor cells after ablation and inhibit the local recurrence of tumors (16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a single tumor biopsy sample With continued advances in cancer research [7][8][9], multiregion genetic analysis of consecutive tumors has shown that each tumor presents diverse, spatially distinct mutations with varied phenotypes within the same tumor [6]. Moreover, a single tumor biopsy sample may be inadequate to develop personalized medicine strategies due to the variations in tumor properties [10,11]. Complexity, diversity, and varied physiological locations for solid tumors [12] lead to additional limitations such as not having enough tumor tissue available for biopsy or not being able to monitor intratumor temporal heterogeneity or metastatic sites [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in developing microfluidics-enabled technologies for exploiting the advantages offered by liquid biopsies is seen in Figure 1, as reflected by the rapid growth of peer-reviewed publications in this area. A search for the keywords "liquid biopsy" in December 2021 in Elsevier's database Scopus yields 11 Therefore, the purpose of this article is to reach a broad audience of science and engineering researchers developing new microscale flow-based technologies for cancer diagnostics. This review article focuses on microfluidic and nanofluidic devices and the various technological approaches implemented through these devices for liquid biopsies with an emphasis on methods and approaches used for isolation, detection, and analysis of extracellular vesicles (EVs) from biofluids.…”
Section: Introductionmentioning
confidence: 99%